Sustainable groundwater management policy strategy in confined aquifers: A SWOT analysis approach - Saves, Faradlillah; Bisri, Mohammad; Siswoyo, Hari; Djati, Moch Sasmito (Journal of Degraded and Mining Lands Management, 2026)
Groundwater management in confined aquifers in Probolinggo Regency is currently under significant pressure due to industrial growth and the impacts of climate change. This study aimed to formulate adaptive policy strategies by synergizing internal technological strengths and the latest regulatory dynamics. The scope of the experiment included identifying internal and external strategic factors through structured interviews and literature reviews validated by technical stakeholders. The method used was the Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis, using the internal factor analysis strategy and external factor analysis strategy matrices to determine the organization's position on the Cartesian diagram. The results of the study showed that internal strengths recorded a total score of 2.4498, while external opportunities recorded a total score of 0.7199. The position analysis places groundwater management in Quadrant I (aggressive) with coordinates (2.3170; 0.5929). The main findings indicated that the organization has a significant competitive advantage through the integration of geospatial data and cutting-edge sensor technology. The formulated strategy includes a transformation towards digital-based management, strengthening science-based conservation through injection technology, and diversifying external funding. This study concludes that implementing aggressive strategies that integrate technological innovation and law enforcement is essential to ensure aquifer sustainability and mitigate the risk of seawater intrusion. The use of this policy roadmap is expected to serve as a guide for local authorities in realizing sustainable groundwater management amid the threat of overexploitation.